(untitled) (Journal of the College of Basic Education, 2019)
The objective of the current research is to determine the degree to which the teachers of the history subject in the preparatory stage have achieved the skills of classroom teaching and their relation to their reasoning skills. To achieve the objectives of the research, ) Of the original research community by (55) teachers and (90) schools distributed in the preparatory and secondary schools day of the six general directorates of education in Baghdad, The researcher then prepared a note form for the teaching skills of the teachers of history, consisting of (45) paragraphs distributed over (6) fields, as well as the construction of a test of reasoning reasoning, which consists of (30) paragraph, and the researcher confirmed their honesty in a number of specialists in teaching methods The researcher applied the observation form and the test of the explanatory thinking on the research sample and extracted the observation stability by finding the correlation coefficient between the researcher and the other observer. The stability of the test of reasoning was done in the method of (Keoder Richardson equation 20). For the Reach results